Perlindungan Hukum Terhadap Kejahatan Cybersquatting Di Indonesia - Reva Amalia (Universitas Islam Indonesia, 2020)
This study aims to determine the definition of cybersquatting and its legal protection in Indonesia. This is a normative research that uses conceptual and statutory approaches. The results of this study conclude that essentially the definition of cybersquatting has not been explicitly defined nor regulated in the laws and regulations in Indonesia. However, cybersquatting can be understood as the act of registering a domain name associated with someone else's company name and then trying to make a profit by selling it to that company. Legal protection against cybersquating is regulated in several laws and regulations, such as Article 23 and Article 38 of Law No. 11 of 2008 on Information and Electronic Transactions, as well as Article 83, Article 100, Article 101, Article 102 of Law No. 20 of 2016 concerning Brands and Geographical Indications. In addition, legal protection for brands’ domain names in regards to cybersquatting can be seen from the government's attempt by delegating responsibility to Indonesian Domain Name Manager (PANDI)